Implications of Literary Reification and the Reifying Reader in Education: A New Epistemological Perspective - Xhindi, Ermir (European Journal of Social Science Education and Research, 2025)
Albanian literature has traditionally had a fundamental systemic place in the institutional life of Albanians, expressed particularly through its special relationship with education. This paper aims to explore a relatively overlooked aspect of the relationship between Albanian literature and education, focusing on how national identity is shaped within literary constructs and the resulting dialectical implications. On these premises, methodologically relying on a Hegelian version of Lukács’s epistemology and Eco’s structuralist model on the interaction of the reader in the construction of the literary text, through the analysis of a textual archetype we have defined as poetics techne for the embodiment of identity, the phenomenon of literary reification and the instrument of the reifying reader. The recognition and functional examination of these tools and their historical, systemic, structural, functional and epistemological implications in education reveal the need for an entirely different perspective in the teaching and interpretation of literature in general. This new corpus should be developed through a dynamic review of the relationship between traditional and constructive pedagogy and literary fiction, to transform the previously passive role of the reader by supporting active cooperative participation.